Indene formation upon borane-induced cyclization of arylallenes, 1, 1-carboboration, and retro-hydroboration. Issue 45 (6th May 2021) - Hasenbeck, Max; Wech, Felix; Averdunk, Arthur; Becker, Jonathan; Gellrich, Urs
Abstract : The formation of pentafluorophenyl indenes upon reaction of arylallenes with B(C6 F5 )3 is reported. Key steps are a 1, 1-carboboration and a retrohydroboration. Abstract : We herein report the reaction of arylallenes with tris(pentafluorophenyl)borane that yields pentafluorophenyl substituted indenes. The tris(pentafluorophenyl)borane induces the cyclization of the allene and transfers a pentafluorophenyl ring in the course of this reaction. A Hammett plot analysis and DFT computations indicate a 1, 1- carboboration to be the C–C bond-forming step.